The role of vasopressin V1A and oxytocin OTR receptors in protective effects of arginine vasopressin against H2O2-induced oxidative stress in H9C2 cells. (4th May 2022) - Ghorbanzadeh, Vajihe; Jafarpour, Afsaneh; Pirnia, Afshin; Pajouhi, Naser; Khaksarian, Mojtaba; Veiskarami, Saeed; Nazari, Afshin
Abstract: Background: Oxidative stress, has been shown to play an important role in the pathophysiology of cardiac remodelling and heart failure. The aim of study is effect of arginine vasopressin (AVP) on apoptosis of cardiomyocyte via its receptors. Materials and methods: The cell viability effect of AVP in H9C2 cardiomyocytes was assayed using the MTT method. The transcription and translation level of apoptosis genes (Bax, Bcl-2, caspase-3) were discovered with qRT-PCR and western blotting. Results: The results showed that vasopressin could reduce apoptosis in cardiomyocytes cell line through downregulation of caspase-3, BAX and upregulation of Bcl-2 ( p  < .001). Also, there was a decrease in anti-apoptosis effect of vasopressin when V1A and OTR receptors were blocked with their antagonists. Discussion: These results suggest that activation of V1A and OTR receptors in H9C2 cells mediate protective effect of vasopressin via regulating apoptosis marker that lead to cell survival under conditions of stress oxidative. Key point: AVP may contribute to the improvement of heart ischaemia through its actions on V1A and OTR receptors.